1977
DOI: 10.1002/jnr.490030202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis sativa on ultrastructure of the synapse in monkey brain

Abstract: Electron microscopic study of brain tissues of monkeys chronically exposed to psychoactive Cannabis showed widening of the synaptic cleft, electron opaque material in the cleft and in pre- and postsynaptic regions, and some "clumping" of synaptic vesicles. In contrast, tissues of control monkeys showed no ultrastructural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Animal studies have demonstrated cellular changes associated with chronic cannabis exposure, especially in prefrontal, hippocampal, and cerebellar regions among mice (Childers & Breivogel, 1998;Ghozland et al, 2002;Misner & Sullivan, 1999), rats (Carta et al, 1998;Chan et al, 1998;Landfield et al, 1988;Romero et al, 1995;Rubino et al, 1997), and primates (Harper et al, 1977;Heath et al, 1980). Morphometric studies conducted among adult marijuana users have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated cellular changes associated with chronic cannabis exposure, especially in prefrontal, hippocampal, and cerebellar regions among mice (Childers & Breivogel, 1998;Ghozland et al, 2002;Misner & Sullivan, 1999), rats (Carta et al, 1998;Chan et al, 1998;Landfield et al, 1988;Romero et al, 1995;Rubino et al, 1997), and primates (Harper et al, 1977;Heath et al, 1980). Morphometric studies conducted among adult marijuana users have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic administration of THC to rats and primates has been shown to result in dose-dependent neurotoxic changes in brain regions that are rich in cannabinoid receptors. Specifi cally, THC-induced neurotoxic eff ects are prominent within the hippocampus (Heath et al ., 1980 ;Scallet et al ., 1987 ;Landfi eld et al ., 1988 ;Chan et al ., 1998 ;Lawston et al ., 2000 ), amygdala (Heath et al ., 1980 ), septum (Harper et al ., 1977 ;Myers and Heath., 1979 ) and cerebral cortex (Harper et al ., 1977 ;Downer et al ., 2001 ). Th ese neurotoxic eff ects include shrinkage of neural cell nuclei and bodies (Heath et al ., 1980 ;Scallet et al ., 1987 ) and reductions in pyramidal cell density (Lawston et al ., 2000 ), dendritic length (Landfi eld et al ., 1988 ) and number of synapses (Heath et al ., 1980 ).…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…(Katona et al, 1999;Domenici et al, 2006). Some previous investigations are pointing toward the enlargement of the synaptic cleft in the septal region under the influence of THC (Harper et al, 1977), although prolonged exposure to WIN55,212-2, (THC agonist) but not THC, desensitized the protective effect. Treating cells that had undergone postsynaptic density protein loss with WIN55,212-2 reversed the loss and enabled recovery of a full complement of synapses (Kim et al, 2008).…”
Section: (Received 4 Th July 2012)mentioning
confidence: 94%
“…These synapses are characterized by a thickened postsynaptic cytoplasmic opacity bordering the region of synaptic contact and by a population of spherical vesicles. Only those fine structures with clear pre-and postsynaptic membranes were included, so as to ensure exact cross-sectional measurement of the cleft (Harper et al, 1977). We used 120 representative figures (60 from the experimental and 60 from the control groups).…”
Section: Perfusion Procedures and Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation